Autosomal Dominant PTH Gene Signal Sequence Mutation in a Family With Familial Isolated Hypoparathyroidism - Cinque, Luigia; Sparaneo, Angelo; Penta, Laura; Mencarelli, Amedea; Rogaia, Daniela; Esposito, Susanna; Fabrizio, Federico Pio; Baorda, Filomena; Verrotti, Alberto; Falorni, Alberto; Stangoni, Gabriela; Hendy, Geoffrey N; et al. (The journal of clinical endocrinology and metabolism, 2017)
ContextFamilial isolated hypoparathyroidism (FIH) is a genetically heterogeneous disorder due to mutations of the calcium-sensing receptor (CASR), glial cells missing-2 (GCM2), guanine nucleotide binding protein α11 (GNA11), or parathyroid hormone (PTH) genes. Thus far, only four cases with homozygous and two cases with heterozygous mutations in the PTH gene have been reported.ObjectiveTo clinically describe an FIH family and identify and characterize the causal gene mutation.DesignGenomic DNA of the family members was subjected to CASR, GCM2, GNA11, and PTH gene mutational analysis. Functional assays were performed on the variant identified.ParticipantsSix subjects of a three-generation FIH family with three affected individuals having severe hypocalcemia and inappropriately low serum PTH.ResultsNo mutations were detected in the CASR, GCM2, and GNA11 genes. A heterozygous variant that segregated with the disease was identified in PTH gene exon 2 (c.41T>A; p.M14K). This missense variant, in the hydrophobic core of the signal sequence, was predicted in silico to impair cleavage of preproPTH to proPTH. Functional assays in HEK293 cells demonstrated much greater retention intracellularly but impaired secretion into the medium of the M14K mutant relative to wild type. The addition of the pharmacological chaperone, 4-phenylbutyric acid, led to a reduction of cellular retention and increased accumulation in the cell medium of the M14K mutant.ConclusionsWe report a heterozygous PTH mutation in an FIH family and demonstrate accumulation of the mutant intracellularly and its impaired secretion. An accurate genetic diagnosis in such hypoparathyroid patients is critical for appropriate treatment and genetic counseling.We report on a heterozygous PTH mutation in an FIH family and demonstrate accumulation of the mutant intracellularly and its impaired secretion.